Uterine bleeding during anticoagulation in women with venous thromboembolism. Issue 151 (March 2017) - Moustafa, Farès; Fernández, Sonia; Fernández-Capitán, Carmen; Nieto, José Antonio; Pedrajas, José María; Visoná, Adriana; Valero, Beatriz; Marchena, Pablo Javier; Braester, Andrei; Monreal, Manuel; ,
ABSTRACT: Background: Women presenting with uterine bleeding during the course of anticoagulant therapy for venous thromboembolism (VTE) present a difficult therapeutic dilemma due to the absence of evidence-based recommendations. Methods: We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) database to assess the clinical characteristics of women presenting with uterine bleeding during anticoagulation for VTE, its frequency, time course, management and 30-day outcomes. Results: As of October 2016, 31, 951 women with VTE were recruited in RIETE. During the course of anticoagulant therapy, 53 (0.17%) developed major uterine bleeding, 118 (0.37%) non-major uterine bleeding and 948 (2.97%) had major bleeding in other sites. Median time elapsed from VTE to bleeding was: 32, 71 and 22 days, respectively. Mean age was: 56±17, 52±20 and 75±14 years, respectively. Women with major uterine bleeding more likely had cancer (51%), anemia (72%), raised platelet count (19%) or recent major bleeding (11%) at VTE presentation than those in the other subgroups. During the first 30 days after bleeding, 17%, 1.7% and 31% of women died, respectively. Of 11 women with uterine bleeding who died, 9 (82%) had cancer, two (18%) died of bleeding and one (9.1%) died of pulmonary embolism after discontinuing anticoagulation. Conclusions: Uterine bleeding during the course of anticoagulation for VTE is not uncommon and mostly affects young women. Those with cancer, anaemia, raised platelet count or recent bleeding at baseline are at an increased risk for uterine bleeding during anticoagulation.